Interfacial Bond Behaviour between FRP Sheet and Concrete under Static and Dynamic Loads - Yuan, Cheng (Curtin University, 2020)
In this thesis, the effects of FRP (Fibre reinforced polymer) configurations, concrete characteristics and strain rate on the bond behaviours between FRP and concrete are investigated by intensive static and dynamic tests, analytical derivations and numerical simulations. Reliable models are proposed to predict the bonding performance. A new epoxy anchor system is proposed to enhance interfacial bond and a wave based sensing approach is used to detect the debonding process with surface mounted piezoceramic transducers.